Abnormalities of pubertal development and gonadal function in Noonan syndrome - Patti, Giuseppa; Scaglione, Marco; Maiorano, Nadia Gabriella; Rosti, Giulia; Divizia, Maria Teresa; Camia, Tiziana; De Rose, Elena Lucia; Zucconi, Alice; Casalini, Emilio; Napoli, Flavia; Di Iorgi, Natascia; Maghnie, Mohamad (Frontiers in Endocrinology, 2023)
Noonan syndrome (NS) is a genetic multisystem disorder characterised by variable clinical manifestations including dysmorphic facial features, short stature, congenital heart disease, renal anomalies, lymphatic malformations, chest deformities, cryptorchidism in males.In this narrative review, we summarized the available data on puberty and gonadal function in NS subjects and the role of the RAS/mitogen-activated protein kinase (MAPK) signalling pathway in fertility. In addition, we have reported our personal experience on pubertal development and vertical transmission in NS.According to the literature and to our experience, NS patients seem to have a delay in puberty onset compared to the physiological timing reported in healthy children. Males with NS seem to be at risk of gonadal dysfunction secondary not only to cryptorchidism but also to other underlying developmental factors including the MAP/MAPK pathway and genetics. Long-term data on a large cohort of males and females with NS are needed to better understand the impact of delayed puberty on adult height, metabolic profile and well-being. The role of genetic counselling and fertility related-issues is crucial.